Every day a Friday journal : how to be happier 7 days a week - Osteen, Joel. Joel Osteen; Osteen, Joel. (New York : FaithWords, 2012)
"The ultimate companion tool to help readers of Every Day a Friday experience a happy and meaningful life every day of the week"--Provided by publisher.
Keywords: Happiness -- Religious aspects -- Christianity; Spiritual journals -- Authorship; Diaries -- Authorship -- Religious aspects -- Christianity